Noncontrast‐enhanced peripheral venography using velocity‐selective magnetization preparation and transient balanced SSFP. Issue 2 (30th March 2015) - Shin, Taehoon; Kligerman, Seth J.; Crawford, Robert S.; Rajagopalan, Sanjay; Gullapalli, Rao P.
Abstract : Purpose: To develop a three‐dimensional (3D) noncontrast‐enhanced (NCE) peripheral magnetic resonance venography (MRV) method and demonstrate its feasibility in vivo. Methods: The proposed MRV pulse sequence consisted of a velocity‐selective (VS) inversion preparation module, inversion delay time (TI), fat inversion pulse, and 3D balanced steady‐state free precession (bSSFP) dummy excitations and readout. The VS preparation module inverted arterial blood, which recovered close to zero magnetization during TI. The TI and the number of dummy excitations (Nnum ) were numerically optimized for maximizing vein‐to‐background contrast and tested in a healthy subject. The proposed MRV of the entire peripheral system, using four‐station acquisition, was performed in six healthy subjects and three peripheral artery patients. Results: The numerical optimization yielded TI = 350 ms and Ndum  = 40, which was supported by the largest vein contrast among the parameters chosen around the optima on in vivo venograms. Four‐station peripheral MRV using the optimized parameters well visualized all major deep veins with high vein‐to‐background contrast. The relative vein contrast ratios were 0.80 ± 0.08, 0.75 ± 0.07, and 0.84 ± 0.06 against the arteries, muscle, and fat, respectively. Conclusion: The proposed NCE MRV using VS preparation and transient bSSFP can generate high‐contrast peripheral venograms directly with a single acquisition. Magn Reson Med 75:653–664, 2016. © 2015 Wiley Periodicals, Inc.